Myelodysplastic Syndromes and Acute Myeloid Leukemia in the Elderly - Klepin, Heidi D. (Clin Geriatr Med, 2016)
Myelodysplastic syndromes and acute myeloid leukemia are hematologic diseases that frequently affect older adults. Treatment is challenging due the morbidity of the disease and toxicity of associated treatments with strategies ranging from best supportive care to hematopoietic stem cell transplantation. Management of older adults with MDS and AML needs to be individualized accounting for both the heterogeneity of disease biology and patient characteristics which can influence life expectancy and treatment tolerance. While treatment options continue to expand for older adults, clinical trials accounting for the heterogeneity of tumor biology and physiologic changes of aging are needed to define optimal standards of care. Incorporating outcomes addressing quality of life, symptoms, maintenance of independence, and health care utilization is necessary to inform patient-centered decision-making. This review highlights key evidence related to management of older adults with MDS and AML and highlights future directions for research.